DETERMINACIÓN DEL EFECTO ANTAGÓNICO DE UN BIOPREPARADO A PARTIR DE UNA CEPA DE Burkholderia cepacia ANTE Fusarium sp EN EL CULTIVO DEL GLADIOLO (Gladiolus sp) - Yuselín Toledo (Cultivos Tropicales, 2002)
The antagonistic effect of a native strain of Burkholderia cepacia against the strains of Fusarium sp race 0 and race 1 was determined. Two in vitro experiments and one in vivo were developed in gladiolus. For the in vivo experiment, plastic pots with approximately 5 kg Red Ferralitic soil from "Las Papas" Experimental Station were used. Healthy and Fusarium-infected white bulbs were used. In the in vitro experiments, an inhibition of 48 to 73.68 % Fusarium (sp) race 0 and of 43.18 to 50.07 % race 1 was demonstrated. In the in vivo experiment, the 90 % of fungal growth was controlled, it proving at the same time plant growth stimulation in gladiolus.